Serang City Environment Community Education About Garbage Banks and Making Garbage Disposal - Suprihatin, Neneng Sri; Nailufaroh, Lulu; Wati, Chinta (EQUATOR SINAR AKADEMIA, 2024)
Human production and consumption processes contribute to global waste problems. The 3R concept (reduce, reuse, and recycle) can help reduce the amount of waste disposed of and generate added value for society. Non-organic waste can be recycled or used for crafts. Organic waste can be collected and processed into biogas, animal feed, or compost. It is very important to conduct socialization and community education to give people an understanding of how to properly manage and process waste. Socialization and community education can be done by creating media such as brochures, pamphlets, and posters about waste management; providing counseling to community groups; inviting people to sort waste into various types; and providing different trash bins for organic and non-organic waste. The results of the activities carried out in the Kaujon Baru Environment with residents of Serang City showed that knowledge about waste sorting is very important, and awareness of how to distinguish organic and inorganic waste must start at home. By providing trash bins that can distinguish organic and non-organic waste, people can become more accustomed to sorting garbage and be more aware of how to process organic waste.